El Leviatán desarmado: el monopolio de las armas en las provincias del Cauca, 1830-1855 (Estudios) - Prado Arellano, Luis Ervin (2019)
The article examines the State’s arms trade monopoly in New Granada in the first half of the nineteenth century as part of the official regime’s policy of exclusive use of force and legitimate violence. Although the goal of the authorities was to keep control over warfare materials, when they promoted the organization of the National Guards in parish districts, they had to distribute arms among the militiamen in order to uphold law and order, as well as discipline in the companies. In addition, the wars of Independence and the civilian conflicts contributed to a wider dispersion of these warfare materials, which ended up in the hands of groups who were challenging the State.